Market-Based Systems of Monetary Control in Developing Countries : Operating Procedures and Related Issues - Wong, Chorng-Huey. (Washington, D.C. : International Monetary Fund, 1991)
This paper reviews issues in the development of a market-based system of monetary control in developing countries. It focuses on the appropriate sequencing of financial reform that would facilitate the transition toward a market-based system and measures required to strengthen the effectiveness of market-based operations. The paper also assesses the effects of financial reform on the demand for money function and discusses the implications for policy formulation and implementation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet